Case study of epidemiological investigation of Dengue Hemorrhagic Fever (DHF) in Blitar City - Aprillia, Shinta Meriza; Peristiowati, Yuli (Institute of Computer Science (IOCS), 2025)
In 2024, there was an upward trend in Dengue Hemorrhagic Fever (DHF) cases in Blitar City, with a total of 135 reported cases. The Incidence Rate (IR) was 92.21 per 100,000 population, and the Case Fatality Rate (CFR) stood at 2.36%. This study aims to investigate DHF cases occurring in three Community Health Centers (Puskesmas) in Blitar City. Using secondary data sources, the highest transmission rate was recorded during the 13th epidemiological week (March 22, 2024) through the 14th week (March 25, 2024). Fatalities were reported in children aged 6 months and 10 years, with the highest Attack Rate found in the 5–14-year age group. In 2024, the Larvae-Free Index (Angka Bebas Jentik/ABJ) in Blitar City was recorded at 94.6%, slightly below the ideal target of >95%. Preventive and promotive efforts were carried out through effective Mosquito Nest Eradication (Eradication of Mosquito Breeding Places/PSN) using the 3M strategy: draining, covering, and recycling water storage containers, along with